2020
DOI: 10.1136/thoraxjnl-2020-214902
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of IPF fibroblastic foci identifies key pathways involved in fibrogenesis

Abstract: IntroductionFibroblastic foci represent the cardinal pathogenic lesion in idiopathic pulmonary fibrosis (IPF) and comprise activated fibroblasts and myofibroblasts, the key effector cells responsible for dysregulated extracellular matrix deposition in multiple fibrotic conditions. The aim of this study was to define the major transcriptional programmes involved in fibrogenesis in IPF by profiling unmanipulated myofibroblasts within fibrotic foci in situ by laser capture microdissection.MethodsThe challenges as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 40 publications
2
23
0
Order By: Relevance
“…Our identification of several Rho GTPases in EVs suggests their potential action on cytoskeleton remodeling by mediating actin filament rearrangement via ROCK [52]. Indeed, interesting studies report that ROCK signaling pathways are involved in myofibroblast differentiation and fibrogenic processes, especially pulmonary fibrosis such as IPF [40,53,54]. Curiously, given the growing attention to Wnt signaling in the regulation of cellular adhesions and its involvement in IPF pathogenic mechanisms, Franco et al reported that Rho GTPases' regulation modulates cell migration and polarity via a βcatenin-independent Wnt pathway [55].…”
Section: Discussionmentioning
confidence: 83%
“…Our identification of several Rho GTPases in EVs suggests their potential action on cytoskeleton remodeling by mediating actin filament rearrangement via ROCK [52]. Indeed, interesting studies report that ROCK signaling pathways are involved in myofibroblast differentiation and fibrogenic processes, especially pulmonary fibrosis such as IPF [40,53,54]. Curiously, given the growing attention to Wnt signaling in the regulation of cellular adhesions and its involvement in IPF pathogenic mechanisms, Franco et al reported that Rho GTPases' regulation modulates cell migration and polarity via a βcatenin-independent Wnt pathway [55].…”
Section: Discussionmentioning
confidence: 83%
“…A previous study using laser capture microdissection of the fibroblastic focus coupled with RNA-sequencing and a novel weighted gene co-expression network analysis showed elevation of genes associated with cell cycle, inflammation/differentiation, translation, and cytoskeleton/cell adhesion [54]. Our analysis identified 100 proteins increased and 211 decreased in the IPF FF relative to non-fibrotic alveoli control (Figure 5A; a full list in Supplemental File 2).…”
Section: The Ipf Fibroblastic Focus Shows Elevated Collagen Biosynthesismentioning
confidence: 54%
“…Our identification of several Rho GTPases in EVs suggests their potential action on cytoskeleton remodeling by mediating actin filament rearrangement via ROCK [52]. Indeed, interesting studies report that ROCK signaling pathways are involved in myofibroblast differentiation and fibrogenic processes, especially pulmonary fibrosis such as IPF [40,53,54]. Curiously, given the growing attention to Wnt signaling in the regulation of cellular adhesions and its involvement in IPF pathogenic mechanisms, Franco et al reported that Rho GTPases' regulation modulates cell migration and polarity via a β-catenin-independent Wnt pathway [55].…”
Section: Discussionmentioning
confidence: 83%